Long noncoding RNA MAPKAPK5-AS1 promoted lipopolysaccharide-induced inflammatory damage in the myocardium by sponging microRNA-124-3p/E2F3 - Weiwei Chen; Guangyuan Gao; Mengjie Yan; Ming Yu; Kaiyao Shi; Ping Yang (Molecular Medicine, 2021)
Abstract Background Myocardial dysfunction caused by sepsis (SIMD) leads to high mortality in critically ill patients. We investigated the function and mechanism of long non-coding RNA MAPKAPK5-AS1 (lncRNA MAPKAPK-AS1) on lipopolysaccharide (LPS)-induced inflammation response in vivo and in vitro. Method Male SD rats were utilized for in vivo experiments. Rat cardiomyocytes (H9C2) were employed for in vitro experiments. Western blotting was employed to measure protein expression, and RT-PCR was performed to measure mRNA expression of inflammation factors. TUNEL and flow cytometry were carried out to evulate cell apoptosis. Result The results showed that the expression of MAPKAPK5-AS1 was increased, while the expression of miR-124-3p was decreased in the inflammatory damage induced by LPS in vivo and in vitro. Knockdown of MAPKAPK5-AS1 reduced LPS-induced cell apoptosis and inflammation response, while overexpression of miR-124-3p weakened the effects of MAPKAPK5-AS1 knockdown on LPS-induced cell apoptosis and inflammation response. Moreover, miR-124-3p was identified as a downstream miRNA of MAPKAPK5-AS1, and E2F3 was a target of miR-214-3p. MAPKAPK5-AS1 knockdown increased the expression of miR-124-3p, while miR-124-3p overexpression reduced the expression of MAPKAPK5-AS1. In addition, miR-124-3p was found to downregulate E2F3 expression in H9C2 cells. Conclusion MAPKAPK5-AS1/miR-124-3p/E2F3 axis regulates LPS-related H9C2 cell apoptosis and inflammatory response.